Submucosal Inferior Turbinectomy to Widen the Surgical Corridor for Endoscopic Endonasal Skull Base Surgery - UOZUMI, Yoichi (Neurol Med Chir (Tokyo), 2020)
The nasal cavity is the exclusive surgical corridor for endoscopic endonasal surgery; however, it is sometimes too narrow to allow extensive surgical maneuvering. Here we show the technique of submucosal inferior turbinectomy (SIT) to widen this surgical corridor. Its effectiveness is evaluated quantitatively by comparing pre- and intraoperative magnetic resonance images. Between March 2015 and October 2018, we performed endoscopic endonasal resection of 57 skull base tumors with 3T intraoperative magnetic resonance imaging (iMRI). Among these resections, cases with previous endonasal surgery and cases for which the iMRI did not cover the entire nasal cavity were excluded. Finally, six cases with and 19 cases without SIT were included in the subsequent retrospective analysis. We measured the dimensions of the narrowest area in inferior nasal cavity on pre- and intraoperative coronal plane gadolinium (Gd)-enhanced T1-weighted MR images using dedicated software, and compared them. The incidence rates of postoperative nasal complaints at outpatient clinics were also compared. Considerable widening of the inferior nasal cavity could be achieved with the SIT, which was statistically significant compared with those without the SIT (111.1 ± 56.5% vs. 39.4 ± 59.4%, respectively; P = 0.0093). In terms of the incidence rate of postoperative nasal complaints at 6 months, there was no statistical difference between the groups (33.3% vs. 15.8%, respectively; P = 0.35). SIT is effective for widening the surgical corridor while keeping nasal function and is especially helpful for lower clivus and laterally extended skull base lesions.